EFL Lecturers' Self-Efficacy in Teaching Speaking: Sources and Beliefs about Teaching Ability - Inge Wahyu Andinda; Amalia Hasanah; Fitri Alya Okta Sukma (Prodi Tadris Bahasa Inggris, 2026)
This study explored EFL lecturers' perceptions on self-efficacy in teaching English speaking at an Indonesian Islamic university. The research addresses the limited empirical studies on self-efficacy in teaching speaking within Indonesian higher education, particularly at the university level. The objectives of this study were to identify EFL lecturers' perceptions of the sources of their self-efficacy in teaching speaking and to describe their perceptions of beliefs about teaching ability in speaking instruction. A qualitative case study design was employed. Data were collected through semi-structured interviews with two EFL lecturers at UIN Raden Fatah Palembang. Data were analyzed using Braun and Clarke's thematic analysis framework. Two major themes emerged. First, sources of self-efficacy included mastery experiences, vicarious experiences, social persuasion, and emotional states. Second, beliefs about teaching ability were reflected in instructional strategies, pedagogical adaptability, and classroom management. The findings suggest that self-efficacy in teaching speaking is shaped by personal, social, and emotional factors. Institutions should support lecturers through constructive feedback, collaborative mentoring, and targeted professional development opportunities.